Does China have a geoeconomic strategy towards Zimbabwe? The case of the Zimbabwean natural resource sector - Annina Kärkkäinen (Springer, 2022)
The Chinese party-state and Chinese companies have become increasingly active in Sub-Saharan Africa, especially in the natural resource sector. Accessing natural resources is assumed to be one of the main goals of both the Chinese government and relevant Chinese companies in resource-rich African countries. In the article, the interplay between Chinese party-state and state-owned enterprises in Zimbabwe is analyzed from the viewpoint of China's geoeconomic strategy. While existing literature has focused on various facets of China's Africa policy, details of collaboration between Chinese party-state and corporate actors remain largely unexamined. In the natural resource sector, such collaboration ranges from negotiating access to natural resources to arranging large Chinese-financed projects repaid or collateralized in natural resources. The article analyzes in detail the cases of three companies that have been involved in such arrangements in Zimbabwe's natural resource sector between 2000 and 2013: NORINCO, AFECC, and CMEC. The central argument advanced in the article is that China's Ministry of Commerce, Eximbank and CDB have pressured the Zimbabwean government to offer resources as collateral for further Chinese loans, in particular in the mid-2000's. The article concludes that while a geoeconomic strategy seems to be in place, its implementation is hindered by the great variety of actors involved.